Effects of Hydroethanolic Extract of Kelussia odoratissima Mozaff. Leaf on Total Antioxidant Capacity and BMP7 Gene Expression in Rat White Adipose Tissue - F Hashemi Shahraki; K Ghatreh Samani; N Zia Jahromi; A Yaghobi (Institue of Medicinal Plants, ACECR, 2018)
Background: Obesity is one of the problems of major concern to todaychr('39')s society. Weight loss has been reported for Kelussia odoratissima Mozaff. Objective: Aim of this research is to examine the effect of this plant extract on plasma total antioxidant capacity and Bone Morphogenetic Protein 7 (BMP7) gene expressions in white adipose tissue (WAT). Methods: Eighty male wistar rats were divided in two prevention (A) and treatment (B) groups and every group were divided to four subgroups. The A for prevention from obesity and B were used for reducing of obesity. WAT was obtained after the study for BMP7 gene expression (with using Real time PCR). Liver sample for catalase activity, blood for measuring of total antioxidant capacity and paraoxonase 1 activity were prepared. Results: Weight loss and BMP7 gene expression was seen only in subgroup that receiving K. odoratissima hydroethanolic extract in the A group. Contrary to expectation, K. odoratissima extract was reduced the total antioxidant capacity in both groups, reduced level of serum paraoxonase 1 activity and increased liver catalase (p value = 0.002) in comparing to the subgroup that received high fat diet (p value = 0.011). Conclusion: K. odoratissima hydroethanolic extract has an effective role in prevention of weight gain and enhanced liver catalase activity. Increasing in BMP7 gene expression probably causes alteration of WAT to brown adipose tissue (BAT). According to this study, consumption of extract can reduce serum total antioxidant capacity and is likely to exacerbate oxidative stress.